The dominant species of natural enemies of Pentatomidae in the peak period. Issue 3 (18th February 2023) - Chen, Shiyan; Cheng, Honghao; Wu, Xiaomeng; Xu, Yue; Zou, Yunding; Bi, Shoudong
Abstract: This paper aims to analyse how to effectively protect and scientifically utilize the natural enemies of Pentatomidae in tea plantations in the peak period. In this paper, the spatial, quantitative and temporal relationships between Pentatomidae and its natural enemies in "Pingyangtezao", "Wuniuzao", "Huangshandayezhong", "Anjibaicha", "Longjing 43″ and "Nongkangzao" tea gardens in Hefei, China were comprehensively compared and analyzed with the methods of geostatistical analysis, gray system analysis and temporal ecotone overlap index analysis. According to the size of the closeness index, the top three natural enemies with the largest sum of spatial, quantitative, and temporal closeness indexes in the six tea gardens were Clubiona japonicola (X7, 16.514), Oxyopes sertatus (X5, 16.390) and Xysticus ephippiafus (X2, 16.270). The size of the ratio between the number of Pentatomidae individuals and natural enemies largely determines whether the natural enemies follow Pentatomidae pests closely or not. The better the growth of tea plantations and the richer the diversity of pest species, the more accurately the predation preference of natural enemies can be reflected. In the control of Pentatomidae, specific analysis should be made according to the occurrence characteristics of target pests in different tea plantations and the basic attributes of tea plantations (species, growth, population characteristics of natural enemies and pests, etc .) in order to scientifically utilize its natural enemies.